Development of Selection Index for Agroforestry Systems - Peter T. Birteeb; Cini Varghese; Seema Jaggi; Mohd. Harun (Journal of the Indian Society of Agricultural Statistics, 2025)
Agroforestry systems involving both tree and crop components usually produce multiple outputs which should all be considered in evaluating the productivity of a system. The problem of multiple outputs arising from tree and crop components can be tackled by developing an index that synthesizes these components into a single value. Therefore, this study aimed to develop a new selection index called Agroforestry System Productivity Index (ASPI) that can be used for easy assessment and comparison of agroforestry systems. The ASPI may be defined as a sum of the relative proportions of the equivalently scaled yields or products of tree and crop components of an agroforestry system. ASPI scores are calculated by converting the outputs of an agroforestry system to a common scale and then ranking the proportions of the converted values for each year of production. The index is shown to be reliable in ranking agroforestry systems and therefore recommended for use in comparing different agroforestry systems involving tree-crop components.